DETERMINATION OF STRENGTHENING CITIZENS IN VILLAGE FUND MANAGEMENT - Santy Aji Sitohang; Talenta Emma Marbun; Wie Shi Wudjud; Sahala Purba (Kajian Akuntansi, 2023)
This research is conducted to explore and analyze whether accountability and citizen involvement can affect the strengthening of residents in managing village funds in the village of Rawang Panca Arga Subdistrict, Asahan Regency, North Sumatra Province. The population in this study is all BPD (Village Representative Agencies) in the village of Rawang Panca Arga Subdistrict. The sample used is a census, meaning all the population is included as a sample, which covers only 30 people when this research was carried out in April and May 2021. The results of this study indicate that only the variable raises has a positive and significant effect on strengthening citizens to manage village funds in the village of Rawang Panca Arga Subdistrict, while the accountability and community involvement variables have no effect, specifically when testing those variables together with the variables of openness, accountability, and residents' condition that have an influence on strengthening citizens in managing village funds. Keywords: Strengthening Citizen, Village Funds, Accountability, Management.